Prevalencies of Ovarian pregnancy confirmed by Histopathological examination: A rare case - Fita Maulina; Purnawan Senoaji; Yuyun Lisnawati (Jurnal Ners, 2026)
Ovarian pregnancy is a rare form of ectopic pregnancy with an estimated incidence ranging from 1 in 2,100 to 1 in 7,000 pregnancies, accounting for only 1–3% of all ectopic cases. Despite its rarity, it remains a diagnostic challenge because its clinical presentation closely resembles tubal pregnancy and ultrasound findings are often inconclusive. Therefore, definitive diagnosis is frequently established during surgery and confirmed through histopathological examination. This study aims to report the prevalence of ovarian pregnancy at Persahabatan General Hospital between January 2015 and April 2019. During the study period, 151 cases of ectopic pregnancy were recorded, of which three were confirmed as ovarian pregnancies, resulting in a prevalence of 0.01%. All patients required surgical management with unilateral salpingo-oophorectomy due to their clinical and hemodynamic conditions. The findings highlight the importance of thorough history taking, early antenatal care, and routine first-trimester transvaginal ultrasound to improve early detection. Management decisions should be individualized based on the patient’s hemodynamic stability to prevent complications and ensure optimal outcomes. Keywords: Ovarian pregnancy, Ectopic pregnancy, Viable ovarian pregnancy